Future Scenarios of the Space Industry in Thailand Using Foresight Methodology - Yuttana Jamjumrus; Suppapol Jaroonvanichkul (International Telecommunications Society (ITS), 2024)
The global space industry is witnessing rapid growth and the emergence of innovative service models that were previously unimaginable . This swift expansion brings uncertainties, presenting both opportunities and challenge s Foresight is a crucial tool for systematically exploring plausible scenarios in the space industry, helping to identify potential impacts and prepare for them. This study explores the future of Thailand's space industry over the next decade using the Foresight methodo logy, specifically the Framework Foresight approach, which includes Framing, Scanning, Forecasting, and Visioning. The research process involved online data collection , an internal workshop within the Office of the National Broadcasting and Telecommunic ations Commission ( interviews a survey, and a workshop with stakeholders in the space industry. From these efforts, 28 trends and emerging issues were identified, leading to the development of four distinct future scenarios. Each scenario was anal yzed for potential implications with corresponding recommendations provided . The findings highlight the need for effective government support and policies, investment support, organizing human resources, and maximizing citizen benefi ts from the space sector in every scenario
Keywords: 330; Foresight; Scenario; Space Industry; Thailand